2011
DOI: 10.1021/jp200966n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Properties and Halogen Bonds of Cyanuric Chloride under High Pressure

Abstract: The effects of high pressure on cyanuric chloride (C(3)N(3)Cl(3)), a remarkable crystal structure dominated by halogen bonds, have been studied by synchrotron X-ray diffraction and Raman spectroscopy in a diamond anvil cell. The results of high pressure experiments revealed that there was no obvious phase transition up to 30 GPa, indicating that halogen bonding is an effective noncovalent interaction to stabilize the crystal structure. Moreover, cyanuric chloride exhibited a high compressibility and a strong a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…If the crystal orientation was not special, the cell position was adjusted to maximize the contrast of the modes between different polarization geometries. In order to quantify the effect of anvil factors on the results of our experiments, we performed high‐pressure polarized Raman experiments on cyanuric chloride; the results of high‐pressure synchrotron X‐ray diffraction and Raman spectroscopy revealed that there was no obvious phase transition up to 30 GPa 25. In this experiment, as shown in Fig.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…If the crystal orientation was not special, the cell position was adjusted to maximize the contrast of the modes between different polarization geometries. In order to quantify the effect of anvil factors on the results of our experiments, we performed high‐pressure polarized Raman experiments on cyanuric chloride; the results of high‐pressure synchrotron X‐ray diffraction and Raman spectroscopy revealed that there was no obvious phase transition up to 30 GPa 25. In this experiment, as shown in Fig.…”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
“…The nature of XB has been widely discussed and is still an active subject of theoretical [ 2 , 4 , 17 , 18 , 19 , 20 ] and experimental chemistry research [ 21 , 22 ]. Most of these works aim to quantify the driving forces of association in the systems studied through different decomposition schemes of the interaction energy.…”
Section: Introductionmentioning
confidence: 99%
“…High pressure has been successfully used to investigate the hydrogen-bonded polymorphic systems, as the application of pressure can provide precise tuning of intermolecular distances. [12][13][14][15] Therefore, hydrogen-bonded polymorphs under high pressures have recently been the subject of extensive research and exhibited rich phenomena. [16][17][18][19][20][21] The orthorhombic and monoclinic polymorphs of L-cysteine are differently affected under identical compression/decompression conditions, implying the kinetic control of pressure-induced phase transitions in crystalline amino acids.…”
Section: Introductionmentioning
confidence: 99%